(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The following article pragmatically presents the subject of the multisectorality nature of tourism as an important segment of tourism economy on the example of the interrelationship between hotel industry and culture. The aim of the discussion is to present possible areas and forms of cooperation between hotels and the representatives of culture as well as to diagnose the benefits of such cooperation. Theoretical considerations have been supported by examples of practices leading to culture promotion and affiliating it with the surroundings of selected hotels in Poland. The analysis primarily confirmed the validity of cooperative activities, but also revealed new functions of culture in the hospitality industry, which in the future, may be implemented in Polish hotel business as an individual characteristic and competitive advantage.